Penerapan Cerita Alkitab Menggunakan Audiovisual untuk Meningkatkan Iman Anak - Antonius Jhon Wilson Neno; Wahyudi Triwiyanto (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
The study was conducted at Hermon Integrated Kindergarten. Initial observations showed the level of faith development of children aged 5-6 years at Hermon Integrated Kindergarten, namely: Children who do not yet believe in the Lord Jesus as Savior have diverse religious backgrounds. Children are afraid to mention the name of the Lord Jesus because parents often forbid and scold them if the name of Jesus is mentioned at home. To overcome this, a creative method is needed because children have different understandings, attitudes, and responses. The first research objective is to describe the application of Bible stories to increase the faith of children aged 5-6 years. Second, to analyze the effectiveness of the application of Bible stories using audiovisuals in increasing the faith of children aged 5-6 years. Third, to analyze the increase in the faith of children aged 5-6 years with the application of Bible stories using audiovisuals. The research subjects were seven children. The research method used was Classroom Action Research using two cycles with six meetings. Based on the results of the recapitulation, the value is that the seven children are in the Very Well Developed (BSB) category. Therefore, it is concluded that the application of Bible stories using audiovisuals can be used in learning activities to increase children's faith. Through the application of audiovisual Bible stories, children learn the Word of God, learn the story of Jesus' life while on earth, believe in Jesus as Lord and Savior of Mankind, and increase the foundation of children's Christian faith.